Prominent immune signatures of T cells are specifically associated with indolent B‐cell lymphoproliferative disorders and predict prognosis. Issue 1 (22nd January 2020) - Yi, Shuhua; Zhang, Yu; Xiong, Wenjie; Chen, Weiwei; Hou, Zhaohua; Yang, Yang; Yan, Yuting; Wei, Yunbo; Cui, Rui; Wang, Huijun; Yu, Zhen; Li, Heng; et al.
Abstract: Objectives: T cells play an essential role in controlling the development of B‐cell lymphoproliferative disorders (BLPDs), but the dysfunction of T cells in BLPDs largely remains elusive. Methods: Using multiplexed flow cytometry, we quantified all major subsets of CD4 + helper T cells (Th) and CD8 + cytotoxic T cells (Tc) in 94 BLPD patients and 66 healthy controls. Statistics was utilised to rank T‐cell signatures that distinguished BLPDs from healthy controls and differentially presented between indolent and aggressive categories. Results: By comparing with healthy controls, we found that the indolent but not aggressive type of BLPDs demonstrated a high degree of T‐cell activation, showing the increase in type I helper T (Th1) cells and follicular B‐helper T (Tfh) cells, both of which strongly associated with the enhanced differentiation of exhaustion‐like effector cytotoxic CD8 + T cells expressing PD‐1 (Tc exhaustion‐like) in indolent BLPDs. Random forest modelling selected a module of T‐cell immune signatures best performing binary classification of all BLPD patients. This signature module was composed of low naïve Th cells and high Th1, Tfh and Tc exhaustion‐like cells which efficiently identified > 85% indolent cases and was, therefore, assigned as the Indolent Dominant Module of T‐cell immune signature. In indolent BLPD patients, a strong bias towards such signatures was found to associate with clinical characteristics of worse prognosis. Conclusion: Our study identified a prominent signature of T‐cell dysregulation specifically for indolent BLPDs, suggesting Th1, Tfh and Tc exhaustion‐like cells represent potential prognostic biomarkers and targets for immunotherapies. Abstract : The dysregulated function of the immune system is a major risk factor for B‐cell lymphoproliferative disorders. Here, we systematically characterized the composition of all the major functional subsets of CD4 + helper T cells and CD8 + cytotoxic T cells in various BLPD subtypes, categorized into indolent and aggressive groups. We identified indolent but not aggressive BLPDs with a prominent T‐cell immune signature of excessive generation of follicular helper T cells and hyperactivation of cytotoxic T cells that are driven towards exhaustion by the expression of PD‐1.